Fatwa on Cryptocurrency as Digital Assets: An Islamic Perspective Amidst Indonesia’s Regulatory Landscape - Latang, Muhammad Aslam; Fathurrahman; Muhammad Faried (MUI Sulawesi Selatan, 2024)
This study aims to analyze the Islamic legal rulings on cryptocurrency as established by the 7th Ijtima Ulama Fatwa Commission of Majelis Ulama Indonesia (MUI) held in November 2021. The research focuses on clarifying the status of cryptocurrency in Islamic law amid growing digital financial innovations. Methodologically, the study employs a qualitative approach based on an in-depth review of fatwas, Islamic jurisprudence, and Indonesian legal frameworks, supported by deliberations involving over 700 scholars, religious leaders, and academics. The findings reveal that MUI declared the use of cryptocurrency as a digital currency haram due to the presence of gharar (uncertainty), dharar (harm), and incompatibility with Indonesian monetary regulations. Similarly, cryptocurrency transactions as commodities or digital assets are deemed invalid because of gharar, dharar, and qimar (gambling), as well as failure to meet the shariah condition of sil’ah (clear ownership). However, an exception applies to cryptocurrencies backed by clear underlying assets, definite value, and proven benefits, which may be permissible. This research contributes original insight into contemporary Islamic finance by addressing cryptocurrency’s evolving legal status within Indonesia’s socio-legal context. The results serve as essential guidance for Muslim communities and policymakers in navigating digital finance consistent with shariah principles.